Penelusuran Sumber Definisi Syāẓ Al-Syāfi’ī: Sebuah Kajian Bibliografis - Reza Pahlevi Dalimunthe; Dedi Masri (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2018)
One of the rules of the validity of the Prophet's traditions is to avoid shāẓ. The definition of shāẓ according to al-Shafi'ī (150-204 H) is a single narrator whose history of hadith contradicts with many other narrators. The majority of hadith scholars such as Ibn al-Ṣalāh (577-643 H), chose the definition over the others. This article focuses on searching the bibliographic source for the definition of shāẓ al-Shāfi’ī with an intertext approach. The object is the works of al-Shafi'ī in the field of hadith and a variety of hadith science literature which includes the definition of shāẓ. This study shows that hadith experts generally agree with the definition of shāẓ al-Shafi'ī because it is easier to apply than other definitions. However, they did not clearly mention the title of al-Shafi'i's essay which he referred to, causing misunderstanding as if the source of the definition of shāẓ was Ibn al-Ṣalāḥ, not al-Shafi'ī. One of these misconceptions stems from the unclear reference of Ibn al-Ṣalāḥ himself. This study shows that the bibliographic results of al-Shafi'i's works and transmission lines of definitions are found that the definition of al-Shafi is not found in al-Risalah, but is sourced from al-Manafib al-Shafi al-Baihaqī